Uji Aktivitas Antioksidan dan Antibakteri Ekstrak dan Hasil Fraksinasi Daun Bandotan (Ageratum conyzoides L.) Terhadap Bakteri Escherichia coli Dan Staphylococcus aureus - Sumiyarni Harahap; Ridwanto Ridwanto; Ainil Fithri Pulungan; Zulmai Rani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Bandotan (Ageratum conyzoides L.) is a plant distributed worldwide, especially in tropical and subtropical regions. Bandotan can be used as a traditional medicine because it contains beneficial phytochemical compounds such as terpenoids, alkaloids, essential oils, saponins, and phenolics that play a role in inhibiting bacterial growth and serving as natural antioxidants. The objective of this research was to determine the antioxidant and antibacterial activity of the extract, n-hexane fraction, and ethyl acetate fraction from bandotan leaves. This research used an experimental method. It included antioxidant testing of the ethanol extract fractions of bandotan leaves (Ageratum conyzoides L.) using the DPPH method and antibacterial testing using Escherichia coli and Staphylococcus aureus bacteria. The phytochemical screening results showed that bandotan leaves contain alkaloids, saponins, tannins, flavonoids, and glycosides. The antioxidant testing for DPPH radical scavenging revealed that the bandotan leaf extract had an IC50 value of 499.3633 μg/ml, the n-hexane fraction had an IC50 value of 945.7837 μg/ml, and the ethyl acetate fraction had an IC50 value of 382.9216 μg/ml, all categorized as very weak antioxidants. Antibacterial testing indicated that the extract, n-hexane fraction, and ethyl acetate fraction of bandotan (Ageratum conyzoides L.) exhibited antibacterial activity, inhibiting the growth of Escherichia coli and Staphylococcus aureus, with strong activity at the highest concentration of 40% and moderate activity at the lowest concentration of 10%. In conclusion, bandotan leaves have very weak antioxidant activity due to the low content of flavonoids and strong antibacterial activity at 40% concentration and weak activity at 10% concentration.